2014
DOI: 10.1111/aos.12356
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound assessment of ocular vascular effects of repeated intravitreal injections of ranibizumab for wet age‐related macular degeneration

Abstract: ABSTRACT.Purpose: Determine the effect of repeated intravitreal injections of ranibizumab (0.5 mg; 0.05 ml) on retrobulbar blood flow velocities (BFVs) using ultrasound imaging quantification in twenty patients with exudative age-related macular degeneration treated for 6 months. Methods: Visualacuity(ETDRS),centralmacularthickness(OCT),peak-systolic, end-diastolic and mean-BFVs in central retinal (CRA), temporal posterior ciliary (TPCA) and ophthalmic (OA) arteries were measured before, 2 days, 3 weeks and 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
0
7
0
1
Order By: Relevance
“…4751 For the 6 eyes that received anti-VEGF treatment, the injections were given based on a treat-and-extend protocol. Therefore, the timing of the injections was different for all 6 eyes.…”
Section: Discussionmentioning
confidence: 99%
“…4751 For the 6 eyes that received anti-VEGF treatment, the injections were given based on a treat-and-extend protocol. Therefore, the timing of the injections was different for all 6 eyes.…”
Section: Discussionmentioning
confidence: 99%
“…В исследованиях Bonnin, посвященных бевацизумабу и ранибизумабу, с помощью ультразвука оценивали скорость глазного кровотока в центральной артерии сетчатки, глазных и задних ресничных артериях. Было отмечено снижение скорости кровото-ка после интравитреального введения антиангиогенных препаратов, что, по мнению авторов, свидетельствовало о возможной способности препарата провоцировать гипоперфузию всего глаза и трактовалось авторами как его временный побочный эффект в отношении регионального сосудистого русла [20,21]. Краткосрочное снижение средних показателей глазного перфузионного давления без выраженного долгосрочного влияния на глазной кровоток также подтвердили в своей работе Lee и соавт.…”
Section: Discussionunclassified
“…Effects of anti-VEGF agents applied intravitreally on ocular hemodynamics were previously identified using CDI (16)(17)(18)20). Toklu et al (16) have reported on the blood flow analysis of CRA in patients with age-related macular degeneration (AMD) after injection of bevacizumab.…”
Section: Discussionmentioning
confidence: 99%
“…Bonnin et al (20) evaluated the effect of repeated intravitreal injections of ranibizumab on retrobulbar blood flow velocities in patients with AMD and found decreases in mean blood flow velocities (BFVs) in the CRA, temporal posterior ciliary artery, and ophthalmic artery (OA) after ranibizumab injections.…”
Section: Discussionmentioning
confidence: 99%